THE EMERGENCE OF THE CLASSICAL ECONOMIC SCHOOL AND ITS EXPERIENCES (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article discusses the emergence of the classical economic school instead of mercantilism. The formation and consolidation of the classical school as a new method of production, as well as the history of the period when the history of the national economy and other social sciences were studied, it is explained what crafts, workshops and manufactures were, the absence of a clear division of labor in it, the emergence of capitalist relations are highlighted. In a different approach from the mercantilists, the representatives of the classical school studied the internal economic relations of capitalist relations that replaced feudalism.